Erectile dysfunction is a marker for obstructive sleep apnea. (2nd April 2016) - Taken, Kerem; Ekin, Selami; Arısoy, Ahmet; Günes, Mustafa; Dönmez, Muhammet İrfan
Abstract: Purpose : To investigate the prevalence of erectile dysfunction (ED) in patients with obstructive sleep apnea (OSA) with and without any other comorbidities. Methods : The patient group was newly diagnosed as having OSA (apnea–hypopnea index [AHI] > 5/h) using a polysomnographic examination. A group of subjects with simple snoring were included into the control group. Clinically relevant comorbidities were systematically assessed in face-to-face interviews. All patients were asked to complete the 15-item International Index of Erectile Function (IIEF-15) questionnaire for the evaluation of ED. The patients with OSA and ED were evaluated according to these comorbidities. Results : Of the 94 patients, 39 patients were excluded because of severe diseases. OSA was observed in 38 (69.1%) of the 55 patients. ED was seen in 24 (63.2%) patients with OSA, and in 8 (47.1%) patients without OSA ( p  > 0.05). There were no statistical differences between the groups' ages, IIEF scores, and body mass index (BMI) scores. There were statistically significant differences between the groups' AHI scores ( p  < 0.05). There was a significant correlation between the groups' AHI scores, BMI, and age ( p  < 0.05). There was no statistically significant difference in patients with OSA, with and without comorbidity in terms of ED. Conclusion : The rate of ED was higher in patients with OSA who had no other comorbidities. Therefore, ED can be a sensitive marker of OSA.